SELFIES AT FUNERALS: REMEDIATING RITUALS OF MOURNING - Gibbs, Martin; Nansen, Bjorn; Carter, Marcus; Kohn, Tamara (AoIR Selected Papers of Internet Research, 2014)
In this paper we examine the controversies surrounding the posting of online ‘selfies at funerals’ that sprung up in late 2013. We argue that the controversies reveal a form of ‘boundary work’ though which participants and publics are negotiating the distinction between legitimate and illegitimate online practices, as well as legitimate and illegitimate responses to death and the rituals associated with death. In Gieryn’s writing, ‘boundary work’ refers to the rhetorical labour scientists engage in to demarcate legitimate science from illegitimate non-science. We use the term to refer to the rhetoric used by participants to position online practices as acceptable or not, especially those associated with grief, bereavement and other matters deserving of gravitas and respect. Woven through these debates are competing threads in which evolving forms of online and youthful expression become entangled with established notions of respectful mourning.